MARKETING COMMUNICATION STRATEGIES FOR INCREASING THE SALES OF DIGITAL PRINTING PRODUCTS - Hamluddin Hamluddin; Marcellino Daffa Arya Wibowo (Makna: Jurnal Kajian Komunikasi, Bahasa, dan Budaya, 2023)
The printing industry, especially digital printing, has experienced rapid advancement amidst fierce competition and increasing technological progress. Marketing communication strategies have become crucial in achieving product marketing goals. This study focuses on understanding marketing communication strategies in the printing industry, specifically digital printing. Utilizing the 7P marketing mix theory, the study employs a qualitative descriptive method with data collection through observation, interviews, and documentation. The post- positivism paradigm is adopted with triangulation technique for data validity. The aim is to uncover company marketing strategies, enhance sales, and identify supporting and hindering factors in marketing. The results of the current study show that the implementation of marketing strategies seem to yield positive effects. The latter points are caused by factors such as product quality, affordable price and excellent after-sales quality. The implications of the results are also discussed.